Chapter 26 Criminalizing dissent - Martin, Greg (Taylor & Francis, 2023)
One could argue that social movements are inherently about human rights. Historically, there have been important movements against slavery, racial discrimination and gender inequality, all of which resonate with international law enshrined in the United Nations (UN) Universal Declaration of Human Rights 1948 . In many respects, human rights reflect citizenship rights, which in the classic formulation of T.H. Marshall (1950) comprise civil, political and social rights. Social movements have been key in securing many of these rights too. In Britain, for example, early welfare movements were organized around what the 1942 Beveridge Report identified as the ‘five evils’ of disease, want, squalor, ignorance, and idleness. Social movement thinkers have argued that these older welfare movements paved the way for newer movements, which ‘operate in and around an already established welfare state system to preserve, extend, deepen and improve service delivery’ (Annetts et al. 2009, p. 10). Examples include lesbian, gay, bisexual and transgendered activism, and eco-welfare movements. However, in the current age of austerity, with dwindling welfare provision, it is questionable whether this remains the case, as many contemporary movements have emerged to protest against new forms of precarity and enduring socioeconomic inequality (Martin 2015a, pp. 78-86).